On Judgements and Propositions - Mahr, Bernd (Electronic Communications of the EASST, 2010)
This article studies some of the relevant and historically inï¬uential conceptions of the notions of âjudgementâ and âpropositionâ and discusses the relationship of these notions in these conceptions. In some detail the conceptions of Aristoteles, Brentano and Twardowski, Frege, Martin-LÃ¶f and of epsilon-theory are presented. A comparison of these conceptions shows fundamental differences which, in a way, illuminate the differences found in the architectures and formal appearances of logics.